MAHAR PERNIKAHAN DALAM PANDANGAN HUKUM DAN PENDIDIKAN ISLAM - Abd. Kafi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2020)
The problem of the obligation of the bridegroom to pay dowry to the prospective wife who is strengthened against the background of the dowry or other conditions in the dowry. So the purpose of this study are: 1) Knowing the basis of dowry law in Islamic view; 2) Knowing the number of dowry from the perspective of the Imam of the school of thought. The research method uses library research and qualitative descriptive analysis. Based on the discussion shows dowry as a mandatory gift from the prospective husband to the prospective wife as a form of sincerity of the prospective husband to cause love for a wife to her future husband, or a mandatory gift from the prospective husband both in the form of objects and services. Religion does not set a minimum or maximum amount of dowry. This is caused by differences in the level and ability of humans to provide it. The implementation of Islamic education lies in the meaning of dowry through knowledge and understanding holistically in schools on the character needs of male and female students, namely: Sincerity and responsibility in providing dowries for male students, wise in using dowries for female students (future wives) and being fair in building a marriage.